Exercise-Training Regulates Apolipoprotein B in Drosophila to Improve HFD-Mediated Cardiac Function Damage and Low Exercise Capacity - Ding, Meng; Zheng, Lan; Li, Qiu Fang; Wang, Wan Li; Peng, Wan Da; Zhou, Meng (Frontiers in Physiology, 2021)
Apolipoprotein B plays an essential role in systemic lipid metabolism and it is closely related to cardiovascular diseases. Exercise-training can regulate systemic lipid metabolism, improve heart function, and improve exercise capacity, but the molecular mechanisms involved are poorly understood. We used a Drosophila model to demonstrate that exercise-training regulates the expression of apoLpp (a homolog of apolipoprotein B) in cardiomyocytes, thereby resisting heart insufficiency and low exercise capacity caused by obesity. The apoLpp is an essential lipid carrier produced in the heart and fat body of Drosophila. In a Drosophila genetic screen, low expression of apoLpp reduced obesity and cardiac dysfunction induced by a high fat diet (HFD). Cardiac-specific inhibition indicated that reducing apoLpp in the heart during HFD reduced the triglyceride content of the whole body and reduced heart function damage caused by HFD. In exercise-trained flies, the result was similar to the knockdown effect of apoLpp. Therefore, apoLpp plays an important role in resisting HFD-induced cardiac insufficiency and low exercise capacity. Although the apoLpp knockdown of cardiomyocytes alleviated damage to heart function, it did not reduce the arrhythmia and low exercise capacity caused by HFD. Exercise-training can improve this condition more effectively and the possible reason for this difference is that exercise-training regulates athletic ability in other ways. Exercise-training during HFD feeding can down-regulate the expression of apoLpp, reduce the whole-body TG levels and cardiac recovery function, and improve exercise capacity. Exercise-training can regulate the expression of apoLpp in cardiomyocytes to resist cardiac function damage and low exercise capacity caused by HFD. The results revealed the relationship between exercise-training and apoLpp and their essential roles in regulating heart function and exercise ability.